A Study of the Performances of Widely Used External Magnetic Field Models in the Outer Zone of the Earth's Radiation Belts by Comparing the Field Observations From Van Allen Probe‐A and the Model Estimations - Xiaochao Yang; Li Wang (Space Weather)
Abstract Using magnetic field observations from Van Allen Probe‐A (VAP‐A), we evaluated the performances of 13 widely used external magnetic field models in the Earth's outer radiation belt region in detail. It is shown that later models tend to match observations better than earlier models except for T03s, which has a top performance similar to the latest TA16_RBF model. Additionally, in its applicable domain from quiet to moderately disturbed geomagnetic conditions, T02 has comparable performance to T03s. In the dusk, dawn and night sectors, highly stretched magnetic fields are seen in both the observations and model output between LmIGRF ∼5.7 and 6.1, which suggests the existence of steep radial gradients in the plasma pressures inside the outer belt region. The contributions from the currents located in the dusk sector during a disturbed period, such as the partial ring current and the substorm current wedge, are not adequately accounted for by the models, and the contribution of field‐aligned currents may also be underestimated. The results of this study will help select reliable external field models for future radiation belt studies and help assess uncertainties caused by the selected models. In addition, detailed analysis of the field components depicted by the empirical models could shed light on understanding the contributions from different current systems in this region.